Severity-adjusted evaluation of initial dialysis on short-term health outcomes in urea cycle disorders - Zielonka, Matthias; Kölker, Stefan; Garbade, Sven; Gleich, Florian; Nagamani, Sandesh C. S.; Gropman, Andrea L.; Druck, Ann-Catrin; Ramdhouni, Nesrine; Göde, Laura; Hoffmann, Georg F.; Posset, Roland (Molecular genetics and metabolism, 2024)
Objective - In individuals with urea cycle disorders (UCDs) and neonatal disease onset, extracorporeal detoxification by continuous kidney replacement therapy is considered the therapeutic method of choice in addition to metabolic emergency treatment to resolve hyperammonemic decompensation. However, the indications for the initiation of dialysis are heterogeneously implemented transnationally, thereby hampering our understanding of (optimal) short-term health outcomes. - Methods - We performed a retrospective comparative analysis evaluating the therapeutic effects of initial dialysis on survival as well as neurocognitive outcome parameters in individuals with UCDs in comparison to a severity-adjusted non-dialyzed control cohort. Overall, 108 individuals with a severe phenotype of male ornithine transcarbamylase deficiency (mOTC-D), citrullinemia type 1 (CTLN1) and argininosuccinic aciduria (ASA) were investigated by stratification based on a recently established and validated genotype-specific disease prediction model. - Results - Mortality is associated with the height of initial peak plasma ammonium concentration, but appears to be independent from treatment with initial dialysis in mOTC-D. However, improved survival after initial dialysis was observed in CTLN1, while there was a trend towards improved survival in ASA. In survivors, annual frequency of (subsequent) metabolic decompensations did not differ between the dialyzed and non-dialyzed cohorts. Moreover, treatment with initial dialysis was not associated with improved neurocognitive outcomes. - Interpretation - The present severity-adjusted comparative analysis reveals that general practice of initial dialysis is neither associated with improved survival in individuals with mOTC-D nor does it differ with regard to the neurocognitive outcome for the investigated UCD subtypes. However, initial dialysis might potentially prove beneficial for survival in CTLN1 and ASA. Clinical trial registration: The UCDC database is recorded at the US National Library of Medicine (https://clinicaltrials.gov).
Gesehen am 27.03.2025